A Flap Design for Alveolar Bone Augmentation: Inverted Double Flap. Issue 4 (August 2016) - Kan, Bahadır
Abstract : Purpose: Although uneventful healing of soft tissue after primary closure of an augmented site represents the crucial point for bone regeneration in oral surgery, the reported incidence of wound dehiscence continues to remain at between 2.5% and 10%. The aim of this new flap design was to decrease complication incidence through double flap closure and stabile keratinized tissue volume. Materials and Methods: Two patients who have partial edentulous alveolus with insufficient bone volume have been reached alveolus reconstruction with autogenous block graft. Before augmentation, flaps have been elevated with 2 layers as inverted double flap. Results: Two patients healed without any complications. The keratinized tissue and vestibule depth were stable when compared with the preoperative positions. Conclusions: This article presents a new flap design that allows twice the coverage of the augmentation site when compared with other techniques and may thus help eliminate problems related to wound healing after augmentation.